Activation of α7 nicotinic acetylcholine receptor retards the development of endometriosis - Meihua Hao; Xishi Liu; Sun-Wei Guo (Reproductive Biology and Endocrinology, 2022)
Abstract Background Women with endometriosis have been shown to have a reduced vagal tone as compared with controls and vagotomy promoted while vagus nerve stimulation (VNS) decelerated the progression of endometriosis in mice. Extensive research also has shown that the activation of the cholinergic anti-inflammatory pathway by VNS activates α7 nicotinic acetylcholine receptor (α7nAChR), potently reducing inflammation. Yet whether α7nAChR plays any role in endometriosis is unknown. We evaluated its expression in normal endometrium, ovarian and deep endometriotic lesions, and evaluated its role in the development of endometriosis. Methods Immunohistochemistry analyses of α7nAChR in endometriotic lesions as well as control endometrium, and quantification of tissue fibrosis by Masson trichrome staining were performed. Mouse experiments were conducted to evaluate the impact of α7nAChR activation or suppression on lesional progression and possible therapeutic effect. Finally, in vitro experiments were conducted to evaluate the effect of activation of α7nAChR on epithelial-mesenchymal transition (EMT), fibroblast-to-myofibroblast transdifferentiation (FMT), smooth muscle metaplasia (SMM) and fibrogenesis in an endometriotic epithelial cell line and primary endometriotic stromal cells derived from ovarian endometrioma tissue samples. Results Immunostaining of α7nAChR was significantly reduced in human endometriotic epithelial cells as compared with their counterpart in normal endometrium. Lesional α7nAChR staining levels correlated negatively with lesional fibrosis and the severity of dysmenorrhea. The α7nAChR agonist significantly impeded the development of endometriotic lesions in mouse models possibly through hindrance of EMT and FMT. It also demonstrated therapeutic effects in mice with induced deep endometriosis. Treatment of endometriotic epithelial and stromal cells with an α7nAChR agonist significantly abrogated platelet-induced EMT, FMT and SMM, and suppressed cellular contractility and collagen production. Conclusions α7nAChR is suppressed in endometriotic lesions, and its activation by pharmacological means can impede EMT, FMT, SMM, and fibrogenesis of endometriotic lesions. As such, α7nAChR can be rightfully viewed as a potential target for therapeutic invention. Trial registration Not applicable.